2022
DOI: 10.1021/acsanm.1c02916
|View full text |Cite
|
Sign up to set email alerts
|

Throughput Optimization of Molybdenum Carbide Nanoparticle Catalysts in a Continuous Flow Reactor Using Design of Experiments

Abstract: Transition metal carbides (TMCs) have attracted significant attention because of their applications toward a wide range of catalytic transformations. However, the practicality of their synthesis is still limited because of the harsh conditions in which most TMCs are prepared. Recently, a solutionphase synthesis of phase-pure α-MoC 1−x nanoparticles was presented. While this synthetic route yielded nanoparticles with exceptional catalytic performance, the reaction parameter space was not explored, and catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The carbon-supported α-MoC 1– x nanoparticle catalysts were evaluated for their performance in the CO 2 hydrogenation reaction following similar conditions to those previously described. , Catalyst (ca. 0.4–0.7 g) was loaded in a 1/4 in.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The carbon-supported α-MoC 1– x nanoparticle catalysts were evaluated for their performance in the CO 2 hydrogenation reaction following similar conditions to those previously described. , Catalyst (ca. 0.4–0.7 g) was loaded in a 1/4 in.…”
Section: Methodsmentioning
confidence: 99%
“…The α-MoC 1– x nanoparticles were evaluated for thermocatalytic CO 2 hydrogenation and shown to exhibit an increased activity on a per-site basis compared to bulk α-MoC 1– x . We further demonstrated that the α-MoC 1– x nanoparticle catalyst synthesis could be scaled up using continuous flow chemistry, while retaining the same catalytic performance as the nanoparticles prepared in the small-scale batch method …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The set of studied nanoparticles includes stoichiometric and non-stochiometric cases, in order to provide information that is expected to be useful for catalysis experiments using these systems, 16,17,21 for instance, in the understanding of their interaction with CO 2 , paving the way towards their improvement through a rational design. 44 For the smallest members of the series, global optimization techniques were used to explore the low-energy isomers. For Mo 4 C 6 and Mo 5 C 6 several isomers exist close in energy to the lowest energy one, where only two low-energy isomers have been found for Mo 6 C 5 , while the same isomer for stoichiometric Mo 6 C 6 was the same for both techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The set of studied nanoparticles includes stoichiometric and non-stochiometric cases, in order to provide information that is expected to be useful for catalysis experiments using these systems, 16,17,21 for instance, in the understanding of their interaction with CO 2 , paving the way towards their improvement through a rational design. 44…”
Section: Discussionmentioning
confidence: 99%